Expansion and Consolidation: The Associate Committee and the Division of Medical Research of the NRC, 1938-1959 - Li, Alison (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1991)
AbstractThe federal government took on the responsibility for the funding and coordination of medical research in 1938 with the creation of the Associate Committee on Medical Research of the National Research Council of Canada. The Associate Committee and its successor, the Division of Medical Research, developed policies and practices which promoted the growth of original investigation in the medical sciences through the Second World War and the post-war expansion. Their work helped to stimulate and institutionalize medical research on a national basis.